'Five pounds for a swadler's head': the Cork anti-Methodist riots of 1749–50*. Issue 263 (15th February 2021) - Lewis, Simon
Abstract: This article constitutes the first large-scale examination of the Cork anti-Methodist riots of 1749–50. Methodist hagiographers have described the rioters as disengaged foot soldiers for Cork's corporation and Anglican clergy. By exploring these disturbances in their religious, political and social context, this paper suggests that the predominantly Catholic rioters were fuelled by their own politico-theological grievances, thereby illuminating the persistence of religious violence in eighteenth-century Ireland. Furthermore, by exploring tensions between Cork Methodists and Baptists, it highlights both the ways in which Methodists sometimes fuelled opposition and the fact that they were not always the sole victims of anti-Methodist violence.